The Fantastic-Grotesque in Beh’Āzin’s “The Snake Stone” - Nahid Shahbazi Moghaddam (مطالعات زبانی و بلاغی)
The present study offers a reading of “The Snake Stone,” penned by Mahmũd Etemādzāde aka. Beh’Āzin (1915-2006), as a tale of fantastic-grotesque. With a preliminary discussion on the grotesque and fantastic in relation to non-western literature, the historical background and the interrelationship of the two modes are briefly sketched through. This is followed by a brief review of Beh’Āzin’s writing style. The snake, as the main motif of the story, is then discussed as a grotesque motif, and The snake stone is dealt with concerning common beliefs and superstitions in popular culture. In a combination of theory and discussion, the story is read through its elements of the grotesque and its fantastic aspects. The study is an analytical library-based research, in which the grotesque is both traced in the narrative mode of the text and in its use of language and certain rhetorical devices. The main aim of discussing “The Snake Stone” as a tale of the fantastic-grotesque is to highlight how this theoretical frame can help to shed light on the socio-cultural aspects of the work and how the link between the author’s ideology and the narrative intricately reinforces the reading beyond the story world. Accordingly, the narrative depicts a miniature of a society where suppression, greed and superstitioFn can be detrimental.